144k views
3 votes
Hi, I need help on this one!

Perform the indicated operation.
a^2 - 2a+1/6 divided by (a^2-1)= _________

The denominator of the resulting fraction is

→ 6(a - 1)
→6(a + 1)
→6

User Shlong
by
5.3k points

1 Answer

4 votes

9514 1404 393

Answer:

(b) 6(a+1)

Explanation:

Common factors are cancelled from numerator and denominator.


\displaystyle(a^2-2a+1)/(6)/(a^2-1)=((a-1)^2)/(6)\cdot(1)/((a-1)(a+1))\\\\=((a-1)(a-1))/(6(a-1)(a+1))=\boxed{(a-1)/(6(a+1))}

The denominator of the result is 6(a+1).

User Manrico Corazzi
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.